Hormones and neuroplasticity: A lifetime of adaptive responses. (January 2022) - Been, Laura E.; Sheppard, Paul A.S.; Galea, Liisa A.M.; Glasper, Erica R.
Highlights: Hormones confer neuroplasticity during life stage transitions in males and females. Sex steroid hormones modulate social recognition behavior in males and females. Gonadal steroid hormones influence paternal behavior and structural plasticity. Peripartum fluctuations in steroid hormones alter the brain and behavior in females. Previous parity reduces hormone levels, brain aging and alters disease risk. Abstract: Major life transitions often co-occur with significant fluctuations in hormones that modulate the central nervous system. These hormones enact neuroplastic mechanisms that prepare an organism to respond to novel environmental conditions and/or previously unencountered cognitive, emotional, and/or behavioral demands. In this review, we will explore several examples of how hormones mediate neuroplastic changes in order to produce adaptive responses, particularly during transitions in life stages. First, we will explore hormonal influences on social recognition in both males and females as they transition to sexual maturity. Next, we will probe the role of hormones in mediating the transitions to motherhood and fatherhood, respectively. Finally, we will survey the long-term impact of reproductive experience on neuroplasticity in females, including potential protective effects and risk factors associated with reproductive experience in mid-life and beyond. Ultimately, a more complete understanding of how hormones influence neuroplasticity throughout the lifespan, beyond development, is necessary for understanding how individuals respond to life changes in adaptive ways.